IMPLIKASI GLOBALISASI EKONOMI DAN PERDAGANGAN BEBAS TERHADAP STABILITAS NILAI RUPIAH - Herlan Firmansyah; Endang Hendra (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2015)
Economic globalization has become a difficult international agenda inevitable by all countries in the world. As well as accelerator movement derivative program of economic globalization, developing free trade (free trade) that has gradually been implemented in most specific regions in the world. For example, NAFTA program that has been effective since January 1, 1994, CAFTA has been in effect as of January 1, 2010 and MEAs will soon be put into effect from December 31, 2015. The goal ultimately is the realization of free trade world as the embodiment of a large agenda that no other is economic globalization. The implication, will materialize interdependent global economy (interdependent) between countries in the world. Including the interdependence of the external value of a country's currency as a unit of account, medium of exchange and store of Value on goods traded within the International transactions. The external value of the currency or commonly known as the exchange rate (exchange rate) is formed as a result of interaction between aggregate demand (aggregate demand) and supply aggregate (aggregate supply) in the money market. Thus, the phenomenon of economic globalization and free trade world that nowadays more and stronger will be the independent variables that can affect currency values of variables as dependent variables of aggregate demand side.